2006
DOI: 10.1007/s10554-006-9175-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of high-density lipoprotein levels and carotid atherosclerotic plaque characteristics by magnetic resonance imaging

Abstract: A low level of high-density lipoprotein cholesterol (HDL-C) is a risk factor for atherosclerotic disease. Magnetic resonance imaging (MRI) can provide detailed information on carotid atherosclerotic plaque size and composition. The purpose of this study was to correlate HDL levels with carotid plaque burden and composition by MRI. Thirty-four patients with coronary artery disease (CAD) receiving simvastatin plus niacin or placebo for both drugs for three years were randomly selected to undergo MRI of carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 26 publications
3
14
1
Order By: Relevance
“…Another area of developing research is the utility of magnetic resonance imaging (MRI) in determining carotid plaque morphology, and determining risk associated with morphologic changes. 21 Zhao et al has demonstrated the modification of carotid plaque morphology measured by MRI utilizing lipid lowering agents. 22 Future analyses would be needed to determine if CRP was an appropriate screening test to identify patients with asymptomatic carotid lesions that could benefit from MRI imaging and directed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another area of developing research is the utility of magnetic resonance imaging (MRI) in determining carotid plaque morphology, and determining risk associated with morphologic changes. 21 Zhao et al has demonstrated the modification of carotid plaque morphology measured by MRI utilizing lipid lowering agents. 22 Future analyses would be needed to determine if CRP was an appropriate screening test to identify patients with asymptomatic carotid lesions that could benefit from MRI imaging and directed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the inherent soft tissue contrast, MRI is desirable as a research tool to describe and possibly separate small changes representing the normal physiology versus changes that will ultimately lead to disease requiring intervention [11]. However, to detect early change in thin vein grafts, current clinically available pulse sequences have limitations primarily related to the tradeoff between spatial resolution, scan time, and signal-to-noise.…”
Section: Discussionmentioning
confidence: 99%
“…High-HDL cholesterol levels are associated with reduced plaque burden, whereas LDL promotes the disease. 21 Second, their small size (≈10 nm) enables them to penetrate the vessel wall more easily than LDL. This led to the development of a vast array of HDL-based contrast agents.…”
Section: R E T R a C T E D A R T I C L Ementioning
confidence: 99%